2013
DOI: 10.1149/2.010306jss
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Process of Formic Acid Pretreatment for Low-Temperature Bonding of Copper Electrodes

Abstract: A new combined process of formic acid pretreatment for low temperature Cu direct bonding was proposed. Cu film and Cu microelectrodes samples were treated by formic acid and successfully bonded together at 200 • C. Cu surface oxide was reduced at 200 • C using formic acid treatment without/with Pt catalyst. Particularly, the treatment with heated Pt catalyst is more effective for Cu surface reduction than that without Pt catalyst or with room temperature Pt catalyst. After formic acid treatment under various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Cu was investigated by previous studies [3,4], according to these, Cu was reduced by formic acid. Therefore, both Ag and Cu surfaces were reduced by formic acid, and it is considered that the reduction of oxidized Ag or Cu layer contributes strong bonding strength.…”
Section: Considerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cu was investigated by previous studies [3,4], according to these, Cu was reduced by formic acid. Therefore, both Ag and Cu surfaces were reduced by formic acid, and it is considered that the reduction of oxidized Ag or Cu layer contributes strong bonding strength.…”
Section: Considerationmentioning
confidence: 99%
“…Therefore, Cu direct bonding requires a chemical mechanical polishing (CMP) to form a smooth and clean surface, and CMP-Cu can be bonded by ion beam activation process [1], or by a hydroxyl bonding [?]. Furthermore, Cu direct bonding was achieved by a bonding method using formic acid for simultaneously bonding and control of the oxide layer on Cu surface at 200 • C [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a low-temperature low-vacuum Cu to Cu bonding process via surface modification with formic acid vapors has been proposed by Suga et al [13][14][15] Taking the advantage of the clean surface, the barriers for the diffusion of Cu atoms is lowered and Cu-Cu bonding at 200°C can be achieved. This vapor-assisted bonding technique has a great potential to extend into the joining for different metal substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is that an actual bonding surface consists of an oxide film and a machined layer; [3][4][5][6][7] therefore, adhesion between surfaces at the bond interface and removal of the oxide film represent necessary requirements to obtain high bond strength. Recently, ultrasonic vibration, [8][9][10][11][12][13] plasma processing, [14][15][16][17][18][19] and organic acid pretreatment [20][21][22][23] have been investigated as methods for breaking and cleaning a superficial oxide film. Indeed, in a previous study, we showed that modification of an oxide film with formic acid greatly improves the strength of bonding between tin surfaces 22) and between tin and copper.…”
Section: Introductionmentioning
confidence: 99%